Factor Analysis of Decreased Body Temperature Redistribution, Linear, and Plateau Phases of Spinal Anesthesia Patients in the Central Surgery Installation Room - Heffy Maulidiyah Wardah; Tri Johan Agus Yuswanto; Imam Subekti (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Perioperative procedures have the potential to reduce body temperature. Many factors influenced this incident. The study aimed to analyze the factors associated with a decrease in body temperature, analyze the relationship between several factors and a decrease in body temperature, and analyze the factors most associated with a decrease in body temperature in the redistribution phase, linear phase, and plateau phase in spinal anesthesia patients in IBS Jombang Regional Hospital. The research used a Cross-Sectional approach with 70 respondents using the Accidental Sampling technique. The independent variables in the study were age, gender, BMI, type of surgery, duration of surgery, irrigation fluid, ASA score, and comorbidities. The dependent variable includes body temperature in the redistribution, linear, and plateau phases of patients after spinal anesthesia. Data was taken through observations of respondents before surgery and ERM data. Data collection was carried out from February – April 2023. Analysis of the relationship between variables used bivariate Chi-Square analysis with an α value set at <0.05. Analysis of the most related variables uses Multivariate Multiple Linear Regression analysis. The majority of patients experience mild hypothermia in the redistribution phase, linear phase, and plateau phase with a temperature of 34⁰C – <36⁰C. Factors associated with a decrease in body temperature were age (p = 0.005), type of surgery (p = 0.015), duration of surgery (p = 0.000), ASA score (p = 0.000), and type of irrigation fluid (p = 0.031). The factors gender (p = 0.333), BMI (p = 0.081), and comorbidities (p = 0.494) did not have a significant relationship with decreasing body temperature. The most dominant factors related were the duration of surgery in the redistribution phase (24.2%), linear phase (32.7%), and plateau phase (27.7%). The factors of age, type of surgery, duration of surgery, ASA score, and type of irrigation fluid were related to a decrease in body temperature. In contrast, gender, BMI, and comorbid factors were not related to a decrease in body temperature, and the most dominant factor was the duration of surgery.